Faktor - Faktor Yang Mempengaruhi Perilaku Pria Dalam Penggunaan KB Pria di wilayah Puskesmas Kecamatan Jatinegara Jakarta Timur - Desfriance Tamu Ina; Herlina Herlina (Jurnal Persada Husada Indonesia, 2018)
Number of male family planning participants for Asia countries as follows; Korea 27%, Sri Lanka 26%, Philippines 24%, Bangladesh 18%, Nepal 18%, Malaysia 16,8%, Chin 11%, Thailand 9%, Pakistan 9% and Indonesia 2%. Amongst Asia countries, Indonesian males participation in the family planning is still low. The family planning programme is part of an integral section in the national development programme and aims to create economic welfare, spiritual and Indonesian social culture so as to achieve a good balance with national productivity ability, also as a measuring stick of factors influencing male behaviour in contraceptive usage in the district area of Jatinegara East Jakarta Communiy Health Centre for the year 2016. This research applied a analytical research with a cross sectional approach. The 80 respondents in the research were married male patients visting the Jatinegara East Jakarta district Communit Health Centre. The results obtained from the chi square test showed the presence of variables influenced by the male contraceptive usage, i.e. attitude (P = 0,014), wives’ support (P=0,000) and friends’ support (P=0,002).